CULTURAL APPROACH (HULU) AS A SIGNIFICANT SOLUTION FOR PLASTIC WASTE HANDLING - Nyoman Mahardika, (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2024)
The problem of plastic waste is a problem that must be handled with top priority because the amount is starting to get out of control. B3 waste, although dangerous and toxic, is not a massive source of emergence involving all humans. It is very difficult to decompose and is a pollutant that is very dangerous for human health. Its destructive power contributes significantly to climate change which disrupts the pattern of life on earth. This research using qualitative methods through participatory observation raises the concept of handling plastic waste problems from two schools of thought, namely upstream and downstream schools. The upstream school uses a cultural approach that emphasizes public awareness campaigns to reduce plastic waste generation. The downstream school of thought handles piles of plastic waste with an emphasis on recycling and reusing plastic waste through the concept of a circular economy. So far the maximum recycling capacity is only 7-9%. With a reduction range of 91% in plastic waste volume, upstream handling with a cultural approach becomes more significant. Upstream handling can be strengthened by using a religious values approach, such as the Tri Hita Karana concept, Swadharma or the concept of 'ngayah', etc. The success of downstream handling should not be made viral because it will discourage community participation in reducing plastic waste. The BumiKita Volunteer Community is one of the communities carrying out awareness movements upstream. Plastic waste clean-up actions are carried out regularly and consistently in several places to spread the message of reducing the use of single-use plastic. Actions are also carried out at cultural and religious events such as festivals, large funerals, melasti ceremonies and so on. Bringing tumblers and the concept of tumblerization is one example of a reduction solution being implemented.